Adventure Reflected In James Dashner's The ScorchTrials Novel (2010): An Individual Psychological Approach - Parlina, Elsa; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2016)
The main issue of this research is adventure. Ii is about someone who journeys to get what he wants. The purpose of this reserach is to analyze The Scorch Trials novel based on the theory of idividual psychological approach. The researcher used qualitative method. The researcher uses two data sources: primary and secondary data. The primary data was The Scorch Trials novel written by James Dashner. The secondary data was supporting data taken from the theory of an individual psychological books, and some articles from the internet related to the novel. The technique of data collection is descriptive analyzis. The technique of analyzing data is descriptive qualitative. Based on an individual psychological analyzis, the researcher finds six aspects such as fictional finalism, striving for succes, inferiority feeling, style of life, social interest and creative self based on The Scorch Trials novel by James Dashner's. Keywords: Adventure, an individual psychological, The Scorch Trials, James Dashner.